Political Management of Migrants Suffering: New Practices by the Mexican State(s) with their Emigrants - Lestage, Françoise (Migraciones Internacionales, 2017)
Since the 1990s, the Mexican federal and state governments have been implementing policies offering financial and administrative aid to Mexican migrants in the United States, and their families, with the procedures involved in daily transnational life. The article argues that a significant portion of this aid forms a structured system of federal and state assistance that the author qualifies as “the political management of migrants suffering”. This system of assistance has specific functions, in particular that of maintaining migrants in the body politic of their home country, as well as effects on social life and on the concept of the nation, mainly because it offers a position for migrants as beneficiaries of public policies (and so as citizens), and simultaneously creates “privileges” by allocating specific forms of aid to them. Gestión política del sufrimiento migrante: Nuevas políticas de los estados mexicanos con sus migrantes Resumen Desde los años noventa del siglo xx, el Estado y los estados mexicanos han ido implementando nuevas políticas públicas dedicadas a los migrantes mexicanos en Estados Unidos y a sus familiares, para apoyarlos económica y administrativamente en sus prácticas cotidianas transnacionales. Este artículo pretende mostrar que una parte importante de esta ayuda pública forma un sistema estructurado que la autora califica como “gestión política del sufrimiento de los migrantes”. Este sistema tiene funciones específicas, en particular, la de mantener a los migrantes en el cuerpo político de su país de origen. También impacta la vida social y el concepto de nación, básicamente porque transforma a los migrantes en beneficiarios de políticas públicas (y así en ciudadanos) que reciben apoyo de formas muy específicas que pueden parecer “privilegios”.